A Randomized, Double-Blind, Placebo-Controlled Trial of Two Doses of Ginkgo Biloba Extract in Dementia of the Alzheimer's Type - Schneider, Lon S.; DeKosky, Steven T.; Farlow, Martin R.; Tariot, Pierre N.; Hoerr, Robert; Kieser, Meinhard (Current Alzheimer Research, 2005)
Context: Previous studies of Ginkgo biloba extract (GbE) in patients with various forms of cognitive impairment or dementia have shown promising results. Objective: To determine the clinical efficacy of GbE in mild to moderate dementia of the Alzheimer type. Design: Randomized, placebo-controlled, double-blind, parallel-group, multicenter trial. Setting: Outpatient clinics of universities and private research centers specialized in dementia. Patients: 513 outpatients with uncomplicated dementia of the Alzheimer's type scoring 10 to 24 on the Mini-Mental State Examination and less than 4 on the modified Hachinski Ischemic Score, free of other serious illnesses and not requiring continuous treatment with any psychoactive drug. Intervention: 26-week treatment with GbE at daily doses of 120 mg or 240 mg or placebo. Main Outcomes: Cognitive subscale of the Alzheimer's Disease Assessment Scale (ADAS-cog), Alzheimer's Disease Cooperative Study Clinical Global Impression of Change (ADCS-CGIC). Results: There were no significant between-group differences for the whole sample. There was little cognitive and functional decline of the placebo-treated patients, however. For a subgroup of patients with neuropsychiatric symptoms there was a greater decline of placebo-treated patients and significantly better cognitive performance and global assessment scores for the patients on GbE. Conclusion: The trial did not show efficacy of GbE, however, the lack of decline of the placebo patients may have compromised the sensitivity of the trial to detect a treatment effect. Thus, the study remains inconclusive with respect to the efficacy of GbE.
Keywords: Ginkgo biloba